Low-temperature reflectance spectra of meteorites: Implications for space missions - E. Caminiti; P. Beck; A. Wargnier; L. Bonal; B. Schmitt; T. Usui (Icarus, 2026)

A histological approach to mortuary variability in Early Bronze Age Transylvania - Nandini Subramaniam; Colin P. Quinn; Jess Beck; Horia Ciugudean; Claes Uhnér; Hannah Lau (Archaeological and Anthropological Sciences, 2026)
The shift from the Copper Age (c. 3600–2700 BCE) to the Early Bronze Age (c. 2700–2000 BCE) in Transylvania (Romania) was a period of significant changes in mortuary practices. We combine bone histology with bioarchaeological and archaeological assessments of mortuary variability to better understand the organization and diversity of funerary practices in the region. Bone histology, the study of microscopic structures of connective tissues in bone, can help disentangle complex mortuary programs. In this study we detail histological analyses of burials from two Early Bronze Age cemeteries: Meteș- La Meteșel , an upland cemetery associated with local Transylvanian communities, and Hăpria, a lowland cemetery associated with Yamnaya migrants. We identify the presence of multiple different pathways from death to burial in primary inhumations and secondary inhumations at these sites. The results here provide new insights into the complex process of cultural exchange during a time of social transformation and high human mobility.

Efficacy of an Inactivated Bacterin Vaccine Against Emerging Streptococcus dysgalactiae in Channel Catfish ( Ictalurus punctatus ) - Brent M. Vuglar; Krishna P. Singha; Craig A. Shoemaker; Benjamin H. Beck; Taylor I. Heckman; Jason W. Abernathy; Julio C. García; Eric Peatman; Timothy J. Bruce (Journal of Fish Diseases, 2026)
Lancefield Group C Streptococcus dysgalactiae recently emerged as a catfish pathogen in the US. Reports from hatcheries suggest S. dysgalactiae causes substantial broodfish loss. We aimed to develop a challenge model and evaluate vaccine efficacy against S. dysgalactiae in juvenile channel catfish ( Ictalurus punctatus ). Three S. dysgalactiae (14–1, 14–24 and 14–25) isolates were tested for virulence. Intracoelomic (IC) injection demonstrated S. dysgalactiae 14–1 was the most virulent. Reisolated 14–1 was used to develop a formalin‐killed cell (FKC) vaccine. Catfish (200) were immunized via IC injection of 100 μL FKC with adjuvant (1:1 v/v), and another 200 catfish were sham vaccinated. Five fish from each group were bled for antibody titre every 14 days. At 28 and 56 days post‐vaccination (dpv), subsets of both groups were challenged with S. dysgalactiae via IC injection (200 μL/fish) in triplicate (20 fish/tank). Cumulative percent mortality was significantly ( p S. dysgalactiae bacterin induced humoral immunity and protected juvenile catfish. Future studies are planned to evaluate this bacterin in broodfish.

Generative diffusion models for agricultural AI: Plant image generation, indoor-to-outdoor translation, and expert preference alignment - Da Tan; Michael Beck; Christopher P. Bidinosti; Robert H. Gulden; Christopher J. Henry (Computers and Electronics in Agriculture, 2026)

ERA5 overestimates land drying trend from 1980 to 2023 by more than 100% - Kaicun Wang; Weihao Mou; Hongze Cai; Changjian Yin; Yun Li; Richard P. Allan; Hylke Beck; Aiguo Dai; Diego G. Miralles; Dongryeol Ryu; Florian Pappenberger (Science Bulletin, 2026)

Low levels of munition compounds in commercially-available seafood from the North Sea and Baltic Sea pose limited risk to human seafood consumers - Tabea Mumberg; Aaron J. Beck; María Martínez-Cabanas; Kathleen J. Gosnell; Martha Gledhill; Eric P. Achterberg (Marine Pollution Bulletin, 2026)

A juvenile arc terrane in the Mid-German Crystalline Zone: constraints from zircon U–Pb–Hf isotope data and implications for pre- to syn-Variscan evolution - Marius Beck; Armin Zeh; Matthias Hinderer; Henri P. Meinaß; Dirk Scheuvens; Axel Gerdes (International Journal of Earth Sciences, 2026)
Presently, little is known about the zircon age–Hf isotope record of (meta)sedimentary rocks exposed in the southernmost part of the Mid-German Crystalline Zone and adjacent Rhenohercynian Domain, preventing detailed reconstructions of the geodynamic evolution in Central Europe. In this study, such data are presented from Late Devonian to Viséan greywackes and granite gneisses of the Palatinate Forest (Mid-German Crystalline Zone) and the Harz Mountains (Rhenohercynian). These provide evidence that clastic sedimentary rocks in both realms were sourced from a so far unrecognized, juvenile oceanic arc terrane, which was initially formed at 490–570 Ma (εHf t up to + 13.0), and internally reworked at ca. 500, 400, 370 and 335 Ma (εHf t = + 2.0 to + 8.4), prior to Variscan collision and post-collisional magmatism at 330 Ma. Late Devonian arc reworking is indicated by zircon U–Pb ages of ca. 370 Ma estimated for the Albersweiler granite gneiss (εHf t = + 3.6 to + 7.7) and an amphibolite-facies paragneiss; other reworking events are indicated by the detrital zircon record. The results of data compilation further suggest that the oceanic arc terrane remained widely isolated from continental input within the Prototethys–Rheic oceanic realm until its collision with Avalonia at 335 Ma. The relics of the arc system became widely dispersed within the Saxothuringian, Rhenohercynian, Teplá-Barrandian, and Moldanubian domains during the Variscan collision and collapse. Graphical abstract

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Ultramafic float rocks at Jezero crater (Mars): excavation of lower crustal rocks or mantle peridotites by impact cratering? - O. Beyssac; E. Clavé; O. Forni; A. Udry; A.C. Pascuzzo; E. Dehouck; P. Beck; L. Mandon; C. Quantin-Nataf; N. Mangold; G. Lopez-Reyes; C. Royer; et al. (Earth and Planetary Science Letters, 2026)

Intensification of extreme precipitation across the Tibetan Plateau and its climatic drivers over 1982−2020 - Yiming Song; Shiqin Xu; Dennis P. Lettenmaier; Hylke E. Beck; Xiaodong Chen; Zhongbo Yu; Ningpeng Dong; Qian Cao; Xiaolei Fu; Zhe Yang; Yuliang Zhang; Matthew F. McCabe (Global and Planetary Change, 2026)

Repeated low-dose copper algaecide treatments promote beneficial phytoplankton and zooplankton communities - Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Journal of Environmental Management, 2025)

UV weathering alters toxicity and chemical composition of consumer plastic leachates - Deedar Nabi; Eric Carmona; Frank Menger; Mara Römerscheid; Stefan Lips; Aaron J. Beck; Alexander Böhme; Hanna Joerss; Annika Jahnke; Deniz Tasdemir; Eric P. Achterberg (Journal of Hazardous Materials, 2025)

Polyelectrolyte metallopolymer particles for efficient PFAS capture and release - Till Rittner; Kevin Staudt; Blandine Boßmann; Ralf Kautenburger; Jean G.A. Ruthes; Christopher W.M. Kay; Volker Presser; Horst P. Beck; Markus Gallei (Desalination, 2025)

Inhibitory effects against SARS-COV-2 main protease of terpenic substances and selenated naphthoquinones - Marcos R. Scheide; Tiago Tizziani; Gabriella B. Souza; Francisco F. de Assis; Eufrânio N. da Silva Júnior; Tainá L. Lubschinski; Ziliani S. Buss; Paula G. F. de Oliveira; Bianca K. Beck; Eduardo M. Dalmarco; Bibiana P. Dambrós; Mario Steindel; et al. (Natural Product Research, 2025)

P28-21 Positive Control Validation of Morris Water Maze and Biel Water Maze – Learning and Memory Assessment Testing Strategies for Weanling and Adult Rats - D.S. Harischandra; S. Beck; J. Proctor-Clarke; A. Hedge; P. Bushdid (Toxicology Letters, 2025)

Multi-millennia slip rate relationships between closely spaced across-strike faults: Temporal earthquake clustering of the Skinos and Pisia Faults, Greece, from in situ 36Cl cosmogenic exposure dating - Sam Mitchell; Claudia Sgambato; Jenni Robertson; Gerald P. Roberts; Joanna P. Faure Walker; Zoë Mildon; Athanassios Ganas; Ioannis Papanikolaou; Francesco Iezzi; Joakim Beck; Steven A. Binnie; Tibor Dunai; et al. (Journal of Structural Geology, 2025)

Co-evolution of organics and water in experimentally shocked Murchison and EET 90628 chondrites - E. Quirico; H. Yabuta; P. Beck; L. Bonal; A. Bardyn; L.R. Nittler; C.M.O’D. Alexander (Geochimica et Cosmochimica Acta, 2025)

Sex and Genotype Affect Mouse Hippocampal Gene Expression in Response to Blast-Induced Traumatic Brain Injury - Kathleen E. Murray; Arun Reddy Ravula; Victoria A. Stiritz; Tara P. Cominski; Vedad Delic; Caralina Marín de Evsikova; Kakulavarapu V. Rama Rao; Namas Chandra; Kevin D. Beck; Bryan J. Pfister; Bruce A. Citron (Molecular Neurobiology, 2025)
Blast-induced traumatic brain injury (bTBI) has been identified as an increasingly prevalent cause of morbidity and mortality in both military and civilian populations over the past few decades. Functional outcomes following bTBI vary widely among individuals, and chronic neurodegenerative effects including cognitive impairments can develop without effective diagnosis and treatment. Genetic predispositions and sex differences may affect gene expression changes in response to bTBI and influence an individual’s probability of sustaining long-term damage or exhibiting resilience and tissue repair. Male and female mice from eight genetically diverse and distinct strains (129S1/SvImJ, A/J, C57BL/6J, CAST/EiJ, NOD/ShiLtJ, NZO/HlLtJ, PWK/PhJ, WSB/EiJ) which encompassed 90% of the genetic variability in commercially available laboratory mice were exposed to a single bTBI (180 kPa) using a well-established shock tube system. Subacute changes in hippocampal gene expression due to blast exposure were assessed using RNA-seq at 1-month post-injury. We identified patterns of dysregulation in gene ontology terms and canonical pathways related to mitochondrial function, ribosomal structure, synaptic plasticity, protein degradation, and intracellular signaling that varied by sex and/or strain, including significant changes in genes encoding respiratory complex I of the electron transport chain in male WSB/EiJ mice and the glutamatergic synapse across more than half of our groups. This study represents a multi-level examination of how genetic variability may influence response to bTBI and provides a foundation for the identification of potential therapeutic targets that could be modulated to improve the health of Veterans and others with histories of blast exposures.

A Novel Approach to Perivitelline Fluid Extraction from Live Water-Activated Eggs from Zebrafish, Danio rerio - Blake A. Lewis; P. Mark Lokman; Caroline W. Beck (Fishes, 2025)
The collection of perivitelline fluid (PVF) from early-stage post-activation zebrafish (Danio rerio) eggs/embryos poses a significant challenge owing to the liability of the egg/embryo to sustain damage and rupture during handling. Rupture of the blastoderm and/or yolk presents a major risk of PVF sample contamination. Previous efforts to extract PVF at such early stages have employed formalin fixation to enhance the structural integrity of the blastoderm and yolk syncytial layer, thereby reducing the likelihood of contamination. While this approach successfully mitigates blastoderm and yolk rupture, formaldehyde fixation may cause issues with downstream proteomic analyses. Recent findings indicate that zebrafish PVF contains a range of maternally inherited proteins involved in innate immune defence. However, current extraction methods compromise the reliability of downstream protein analyses, raising concerns that fixation-induced protein crosslinking may obscure the presence of maternally inherited proteins during the earliest stages of development. The micro-aspiration technique described here allows for the precise extraction of PVF from living, water-activated eggs with minimal disruption to the blastodisc and yolk. This method reduces the risk of contamination from other non-target proteinaceous egg sources and eliminates the need for formalin fixation, thereby improving the integrity of PVF samples and enhancing the reliability of subsequent downstream analyses.

The mineralogical composition of Jezero Crater Western Fan: Multigaussian modeling of Perseverance/SuperCam near-infrared observations and overview of major units - C. Royer; F. Poulet; R.C. Wiens; F. Montmessin; P. Beck; O. Beyssac; É. Clavé; E. Dehouck; T. Fouchet; J.R. Johnson; L. Mandon; S. Bernard; et al. (Icarus, 2025)

Erratum to “Screening the release of chemicals and microplastic particles from diverse plastic consumer products into water under accelerated UV weathering conditions” [J Hazard Mater 477 (2024) 135256] - Frank Menger; Mara Römerscheid; Stefan Lips; Ole Klein; Deedar Nabi; Jürgen Gandrass; Hanna Joerss; Katrin Wendt-Potthoff; Daria Bedulina; Tristan Zimmermann; Mechthild Schmitt-Jansen; Carolin Huber; et al. (Journal of Hazardous Materials, 2025)

How many Macropsychanthus (Leguminosae: Papilionoideae) species are found in Bolivia? Clarification of the taxa, a new species and an identification key - Andrés Fonseca-Cortés; Cristiane Snak; Stephan G. Beck; Ruth P. Clark; Bente Klitgaard; Rosember Hurtado Ulloa; Leslie Cayola Perez; Carla Maldonado; Luciano Paganucci de Queiroz (Kew Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

From hydrated silica to quartz: Potential hydrothermal precipitates found in Jezero crater, Mars - P. Beck; O. Beyssac; E. Dehouck; S. Bernard; M. Pineau; L. Mandon; C. Royer; E. Clavé; S. Schröder; O. Forni; R. Francis; N. Mangold; et al. (Earth and Planetary Science Letters, 2025)

Correction to: Novel environmental variables help explain winter weather effects on activity and habitat selection of greater sage-grouse along the border of Colorado and Wyoming, USA - Caitlyn P. Wanner; Aaron C. Pratt; Adele K. Reinking; Glen E. Liston; Jeffrey L. Beck (International Journal of Biometeorology, 2025)

Widespread environmental contamination from relic munitions in the southwestern Baltic Sea - Aaron J. Beck; Martha Gledhill; Ulf Gräwe; Mareike Kampmeier; Anja Eggert; Christian Schlosser; Beate Stamer; Jens Greinert; Eric P. Achterberg (Chemosphere, 2025)

Evaluating the tolerance of harmful algal bloom communities to copper - Ashley V. Hennessey; Michael B. McDonald; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Environmental Pollution, 2025)

Thermal metamorphism and volatile evolution in unequilibrated ordinary chondrites: Implications for the delivery of hydrogen to terrestrial planets - L.G. Vacher; J. Eschrig; L. Bonal; W. Fujiya; L. Flandinet; P. Beck (Geochimica et Cosmochimica Acta, 2025)

Novel environmental variables help explain winter weather effects on activity and habitat selection of greater sage-grouse along the border of Colorado and Wyoming, USA - Caitlyn P. Wanner; Aaron C. Pratt; Adele K. Reinking; Glen E. Liston; Jeffrey L. Beck (International Journal of Biometeorology, 2025)

Uncertainty quantification for severe-accident reactor modelling: Results and conclusions of the MUSA reactor applications work package - S. Brumm; F. Gabrielli; V. Sanchez Espinoza; A. Stakhanova; P. Groudev; P. Petrova; P. Vryashkova; P. Ou; W. Zhang; A. Malkhasyan; L.E. Herranz; R. Iglesias Ferrer; et al. (Annals of Nuclear Energy, 2025)

Low temperature phase transitions in the visible and near-infrared (VNIR) reflectance spectra of (NH4)2HPO4 and (NH4)HSO4 salts - M. Fastelli; B. Schmitt; P. Beck; O. Poch; A. Zucchini; P. Comodi (Icarus, 2025)

Soil diversity at Jezero crater and Comparison to Gale crater, Mars - A. Cousin; P.-Y. Meslin; O. Forni; O. Beyssac; E. Clavé; E. Hausrath; P. Beck; E. Dehouck; S. Schröder; T. Fouchet; C. Bedford; J. Johnson; et al. (Icarus, 2025)

GALÆXI: Solving complex compressible flows with high-order discontinuous Galerkin methods on accelerator-based systems - Marius Kurz; Daniel Kempf; Marcel P. Blind; Patrick Kopper; Philipp Offenhäuser; Anna Schwarz; Spencer Starr; Jens Keim; Andrea Beck (Computer Physics Communications, 2025)

Effect of PLGA raw materials on in vitro and in vivo performance of drug-loaded microspheres - Desheng Liang; Jennifer Walker; Peter S. Schwendeman; Aishwarya Chandrashekar; Rose Ackermann; Karl F. Olsen; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2025)

A Probabilistic View of Forbidden Links: Their Prevalence and Their Consequences for the Robustness of Plant–Hummingbird Communities - François Duchenne; Elisa Barreto; Esteban A. Guevara; Holger Beck; Carolina Bello; Rafaela Bobato; Daniela Bôlla; Emanuel Brenes; Nicole Büttner; Ana P. Caron; Nelson Chaves‐Elizondo; María J. Gavilanes; et al. (Ecology Letters, 2025)
The presence in ecological communities of unfeasible species interactions, termed forbidden links, due to physiological or morphological exploitation barriers has been long debated, but little direct evidence has been found. Forbidden links are likely to make ecological communities less robust to species extinctions, stressing the need to assess their prevalence. Here, we used a dataset of plant–hummingbird interactions, coupled with a Bayesian hierarchical model, to assess the importance of exploitation barriers in determining species interactions. We found evidence for exploitation barriers between flowers and hummingbirds across the 32 studied communities; however, the proportion of forbidden links changed drastically among communities because of changes in trait distributions. The higher the proportion of forbidden links, the more they decreased network robustness because of constraints on interaction rewiring. Our results suggest that exploitation barriers are not rare in plant–hummingbird communities and have the potential to limit the rescue of species experiencing partner extinction.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Screening the release of chemicals and microplastic particles from diverse plastic consumer products into water under accelerated UV weathering conditions - Frank Menger; Mara Römerscheid; Stefan Lips; Ole Klein; Deedar Nabi; Jürgen Gandrass; Hanna Joerss; Katrin Wendt-Potthoff; Daria Bedulina; Tristan Zimmermann; Mechthild Schmitt-Jansen; Carolin Huber; et al. (Journal of Hazardous Materials, 2024)

Building equity into public park and recreation service investment: A review of public agency approaches - Helen Beck; Rachel Berney; Brian Kirk; Ken P. Yocom (Landscape and Urban Planning, 2024)

Comparison of dental topography of marmosets and tamarins (Callitrichidae) to other platyrrhine primates using a novel freeware pipeline - Dorien de Vries; Mareike C. Janiak; Romina Batista; Jean P. Boubli; Ian B. Goodhead; Emma Ridgway; Doug M. Boyer; Elizabeth St. Clair; Robin M. D. Beck (Journal of Mammalian Evolution, 2024)
Dental topographic metrics (DTMs), which quantify different aspects of the shape of teeth, are powerful tools for studying dietary adaptation and evolution in mammals. Current DTM protocols usually rely on proprietary software, which may be unavailable to researchers for reasons of cost. We address this issue in the context of a DTM analysis of the primate clade Platyrrhini (“New World monkeys”) by: 1) presenting a large comparative sample of scanned second lower molars (m2s) of callitrichids (marmosets and tamarins), previously underrepresented in publicly available datasets; and 2) giving full details of an entirely freeware pipeline for DTM analysis and its validation. We also present an updated dietary classification scheme for extant platyrrhines, based on cluster analysis of dietary data extracted from 98 primary studies. Our freeware pipeline performs equally well in dietary classification accuracy of an existing sample of platyrrhine m2s (excluding callitrichids) as a published protocol that uses proprietary software when multiple DTMs are combined. Individual DTMs, however, sometimes showed very different results in classification accuracies between protocols, most likely due to differences in smoothing functions. The addition of callitrichids resulted in high classification accuracy in predicting diet with combined DTMs, although accuracy was considerably higher when molar size was included (90%) than excluded (73%). We conclude that our new freeware DTM pipeline is capable of accurately predicting diet in platyrrhines based on tooth shape and size, and so is suitable for inferring probable diet of taxa for which direct dietary information is unavailable, such as fossil species.

Maize terpene synthase 1 impacts insect behavior via the production of monoterpene volatiles β-myrcene and linalool - Jessica P. Yactayo-Chang; Geoffrey T. Broadhead; Robert J. Housler; Marcio F.R. Resende; Kashish Verma; Joe Louis; Gilles J. Basset; John J. Beck; Anna K. Block (Phytochemistry, 2024)

Main outcomes of the Phebus FPT1 uncertainty and sensitivity analysis in the EU-MUSA project - F. Mascari; A. Bersano; M. Massone; G. Agnello; O. Coindreau; S. Beck; L. Tiborcz; S. Paci; M. Angelucci; L.E. Herranz; R. Bocanegra; Y. Pontillon; et al. (Annals of Nuclear Energy, 2024)

Detectability of carbon with ChemCam LIBS: Distinguishing sample from Mars atmospheric carbon, and application to Gale crater - P. Beck; P.Y. Meslin; A. Fau; O. Forni; O. Gasnault; J. Lasue; A. Cousin; S. Schröder; S. Maurice; W. Rapin; R.C. Wiens; A.M. Ollila; et al. (Icarus, 2024)

World war munitions as a source of mercury in the southwest Baltic Sea - Kathleen J. Gosnell; Lars-Eric Heimbürger-Boavida; Aaron J. Beck; Peter R. Ukotije-Ikwut; Eric P. Achterberg (Chemosphere, 2023)

The Database of European Forest Insect and Disease Disturbances: DEFID2 - Giovanni Forzieri; Loïc P. Dutrieux; Agata Elia; Bernd Eckhardt; Giovanni Caudullo; Flor Álvarez Taboada; Alessandro Andriolo; Flavius Bălăcenoiu; Ana Bastos; Andrei Buzatu; Fernando Castedo Dorado; Lumír Dobrovolný; et al. (Global Change Biology, 2023)
Insect and disease outbreaks in forests are biotic disturbances that can profoundly alter ecosystem dynamics. In many parts of the world, these disturbance regimes are intensifying as the climate changes and shifts the distribution of species and biomes. As a result, key forest ecosystem services, such as carbon sequestration, regulation of water flows, wood production, protection of soils, and the conservation of biodiversity, could be increasingly compromised. Despite the relevance of these detrimental effects, there are currently no spatially detailed databases that record insect and disease disturbances on forests at the pan‐European scale. Here, we present the new Database of European Forest Insect and Disease Disturbances (DEFID2). It comprises over 650,000 harmonized georeferenced records, mapped as polygons or points, of insects and disease disturbances that occurred between 1963 and 2021 in European forests. The records currently span eight different countries and were acquired through diverse methods (e.g., ground surveys, remote sensing techniques). The records in DEFID2 are described by a set of qualitative attributes, including severity and patterns of damage symptoms, agents, host tree species, climate‐driven trigger factors, silvicultural practices, and eventual sanitary interventions. They are further complemented with a satellite‐based quantitative characterization of the affected forest areas based on Landsat Normalized Burn Ratio time series, and damage metrics derived from them using the LandTrendr spectral–temporal segmentation algorithm (including onset, duration, magnitude, and rate of the disturbance), and possible interactions with windthrow and wildfire events. The DEFID2 database is a novel resource for many large‐scale applications dealing with biotic disturbances. It offers a unique contribution to design networks of experiments, improve our understanding of ecological processes underlying biotic forest disturbances, monitor their dynamics, and enhance their representation in land‐climate models. Further data sharing is encouraged to extend and improve the DEFID2 database continuously. The database is freely available at https://jeodpp.jrc.ec.europa.eu/ftp/jrc‐opendata/FOREST/DISTURBANCES/DEFID2/ .

Reflectance spectra of mascagnite and salammoniac minerals with varying viewing geometry - M. Fastelli; B. Schmitt; P. Beck; O. Poch; A. Zucchini; F. Frondini; P. Comodi (Icarus, 2023)

Compositional shifts of alpine plant communities across the high Andes - F. Cuesta; J. Carilla; L. D. LLambí; P. Muriel; M. V. Lencinas; R. I. Meneses; K. J. Feeley; H. Pauli; N. Aguirre; S. Beck; A. Bernardi; S. Cuello; et al. (Global Ecology and Biogeography, 2023)
Aim Climate change is transforming mountain summit plant communities worldwide, but we know little about such changes in the High Andes. Understanding large‐scale patterns of vegetation changes across the Andes, and the factors driving these changes, is fundamental to predicting the effects of global warming. We assessed trends in vegetation cover, species richness (SR) and community‐level thermal niches (CTN) and tested whether they are explained by summits' climatic conditions and soil temperature trends. Location High Andes. Time period Between 2011/2012 and 2017/2019. Major taxa studied Vascular plants. Methods Using permanent vegetation plots placed on 45 mountain summits and soil temperature loggers situated along a ~6800 km N‐S gradient, we measured species and their relative percentage cover and estimated CTN in two surveys (intervals between 5 and 8 years). We then estimated the annual rate of changes for the three variables and used generalized linear models to assess their relationship with annual precipitation, the minimum air temperatures of each summit and rates of change in the locally recorded soil temperatures. Results Over time, there was an average loss of vegetation cover (mean = −0.26%/yr), and a gain in SR across summits (mean = 0.38 species m 2 /yr), but most summits had significant increases in SR and vegetation cover. Changes in SR were positively related to minimum air temperature and soil temperature rate of change. Most plant communities experienced shifts in their composition by including greater abundances of species with broader thermal niches and higher optima. However, the measured changes in soil temperature did not explain the observed changes in CTN. Main conclusions High Andean vegetation is changing in cover and SR and is shifting towards species with wider thermal niche breadths. The weak relationship with soil temperature trends could have resulted from the short study period that only marginally captures changes in vegetation through time.

Spectral and mineralogical effects of heating on CM chondrite and related asteroids - S. Sidhu; E.A. Cloutis; P. Mann; D. Applin; T. Hiroi; K. Mengel; T. Kareta; V. Reddy; P. Beck; S.A. Mertzman (Icarus, 2023)

Considerations when modelling human diseases - Amanda P. Beck (Journal of Comparative Pathology, 2023)

If you give a mouse a mutation: comparing the therapeutic utility of renowned mouse models of human cancers - Elayna M. Shanker; Amanda P. Beck (Journal of Comparative Pathology, 2023)

Physical and biogeochemical controls on seasonal iron, manganese, and cobalt distributions in Northeast Atlantic shelf seas - Xue-Gang Chen; Dagmara Rusiecka; Martha Gledhill; Angela Milne; Amber L. Annett; Aaron Joseph Beck; Antony J. Birchill; Maeve C. Lohan; Simon Ussher; Eric P. Achterberg (Geochimica et Cosmochimica Acta, 2023)

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

Evaluation of aqueous magnesium concentration on performance of Pacific white shrimp (Litopenaeus vannamei) cultured in low salinity water of West Alabama, USA - David P. Hernández; Hisham A. Abdelrahman; Harsha S.C. Galkanda-Arachchige; Anita M. Kelly; Ian A.E. Butts; D. Allen Davis; Benjamin H. Beck; Luke A. Roy (Aquaculture, 2023)

Long-term growing season aridity and grazing seasonality effects on perennial grass biomass in a Chihuahuan Desert rangeland - Sophia N. Lasché; Ryan W.R. Schroeder; Matthew M. McIntosh; Jacob E. Lucero; Sheri A. Spiegal; Micah P. Funk; Reldon F. Beck; Jerry L. Holechek; Akasha M. Faist (Journal of Arid Environments, 2023)

Total evidence phylogeny of platyrrhine primates and a comparison of undated and tip-dating approaches - Robin M.D. Beck; Dorien de Vries; Mareike C. Janiak; Ian B. Goodhead; Jean P. Boubli (Journal of Human Evolution, 2023)

In vitro degradation and erosion behavior of commercial PLGAs used for controlled drug delivery - Jennifer Walker; Jason Albert; Desheng Liang; Jing Sun; Richard Schutzman; Raj Kumar; Cameron White; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2023)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Two hundred and five newly assembled mitogenomes provide mixed evidence for rivers as drivers of speciation for Amazonian primates - Mareike C. Janiak; Felipe E. Silva; Robin M. D. Beck; Dorien de Vries; Lukas F. K. Kuderna; Nicole S. Torosin; Amanda D. Melin; Tomàs Marquès‐Bonet; Ian B. Goodhead; Mariluce Messias; Maria N. F. da Silva; Iracilda Sampaio; et al. (Molecular Ecology, 2022)
Mitochondrial DNA remains a cornerstone for molecular ecology, especially for study species from which high‐quality tissue samples cannot be easily obtained. Methods using mitochondrial markers are usually reliant on reference databases, but these are often incomplete. Furthermore, available mitochondrial genomes often lack crucial metadata, such as sampling location, limiting their utility for many analyses. Here, we assembled 205 new mitochondrial genomes for platyrrhine primates, most from the Amazon and with known sampling locations. We present a dated mitogenomic phylogeny based on these samples along with additional published platyrrhine mitogenomes, and use this to assess support for the long‐standing riverine barrier hypothesis (RBH), which proposes that river formation was a major driver of speciation in Amazonian primates. Along the Amazon, Negro, and Madeira rivers, we found mixed support for the RBH. While we identified divergences that coincide with a river barrier, only some occur synchronously and also overlap with the proposed dates of river formation. The most compelling evidence is for the Amazon river potentially driving speciation within bearded saki monkeys ( Chiropotes spp.) and within the smallest extant platyrrhines, the marmosets and tamarins. However, we also found that even large rivers do not appear to be barriers for some primates, including howler monkeys ( Alouatta spp.), uakaris ( Cacajao spp.), sakis ( Pithecia spp.), and robust capuchins ( Sapajus spp.). Our results support a more nuanced, clade‐specific effect of riverine barriers and suggest that other evolutionary mechanisms, besides the RBH and allopatric speciation, may have played an important role in the diversification of platyrrhines.

Correction to: Characterization of commercial PLGAs by NMR spectroscopy - Jing Sun; Jennifer Walker; Moritz Beck‑Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2022)

Characterization of commercial PLGAs by NMR spectroscopy - Jing Sun; Jennifer Walker; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2022)

The Dewey Monitor: Pulse Oximetry can Warn of Hypoxia in an Immersed Rebreather Diver in Multiple Scenarios - Rachel M. Lance; Michael J. Natoli; Fabio Di Pumpo; Timothy P. Beck; Alan Gatrell; Gregory J. Brown; Derek Schocken; Richard E. Moon (Annals of Biomedical Engineering, 2022)

Zea mays Volatiles that Influence Oviposition and Feeding Behaviors of Spodoptera frugiperda - Jessica P. Yactayo-Chang; Jorrel Mendoza; Steven D. Willms; Caitlin C. Rering; John J. Beck; Anna K. Block (Journal of Chemical Ecology, 2021)

Generalized olfactory detection of floral volatiles in the highly specialized Greya-Lithophragma nursery pollination system - Florian P. Schiestl; Erika A. Wallin; John J. Beck; Magne Friberg; John N. Thompson (Arthropod-Plant Interactions, 2021)
Volatiles are of key importance for host-plant recognition in insects. In the pollination system of Lithophragma flowers and Greya moths, moths are highly specialized on Lithophragma , in which they oviposit and thereby pollinate the flowers. Floral volatiles in Lithophragma are highly variable between species and populations, and moths prefer to oviposit into Lithophragma flowers from populations of the local host species. Here we used gas chromatography coupled with electroantennographic detection (GC-EAD) to test whether Greya moths detect specific key volatiles or respond broadly to many volatiles of Lithophragma flowers. We also addressed whether olfactory detection in Greya moths varies across populations, consistent with a co-evolutionary scenario. We analyzed flower volatile samples from three different species and five populations of Lithophragma occurring across a 1400 km range in the Western USA, and their sympatric female Greya politella moths. We showed that Greya politella detect a broad range of Lithophragma volatiles, with a total of 23 compounds being EAD active. We chemically identified 15 of these, including the chiral 6, 10, 14-trimethylpentadecan-2-one (hexahydrofarnesyl acetone), which was not previously detected in Lithophragma . All investigated Lithophragma species produced the (6 R , 10 R )-enantiomer of this compound. We showed that Greya moths detected not only volatiles of their local Lithophragma plants, but also those from allopatric populations/species that they not encounter in local populations. In conclusion, the generalized detection of volatiles and a lack of co-divergence between volatiles and olfactory detection may be of selective advantage for moths in tracking hosts with rapidly evolving, chemically diverse floral volatiles.

A research framework for projecting ecosystem change in highly diverse tropical mountain ecosystems - Jörg Bendix; Nicolay Aguire; Erwin Beck; Achim Bräuning; Roland Brandl; Lutz Breuer; Katrin Böhning-Gaese; Mateus Dantas de Paula; Thomas Hickler; Jürgen Homeier; Diego Inclan; Christoph Leuschner; et al. (Oecologia, 2021)
Tropical mountain ecosystems are threatened by climate and land-use changes. Their diversity and complexity make projections how they respond to environmental changes challenging. A suitable way are trait-based approaches, by distinguishing between response traits that determine the resistance of species to environmental changes and effect traits that are relevant for species' interactions, biotic processes, and ecosystem functions. The combination of those approaches with land surface models (LSM) linking the functional community composition to ecosystem functions provides new ways to project the response of ecosystems to environmental changes. With the interdisciplinary project RESPECT, we propose a research framework that uses a trait-based response-effect-framework (REF) to quantify relationships between abiotic conditions, the diversity of functional traits in communities, and associated biotic processes, informing a biodiversity-LSM. We apply the framework to a megadiverse tropical mountain forest. We use a plot design along an elevation and a land-use gradient to collect data on abiotic drivers, functional traits, and biotic processes. We integrate these data to build the biodiversity-LSM and illustrate how to test the model. REF results show that aboveground biomass production is not directly related to changing climatic conditions, but indirectly through associated changes in functional traits. Herbivory is directly related to changing abiotic conditions. The biodiversity-LSM informed by local functional trait and soil data improved the simulation of biomass production substantially. We conclude that local data, also derived from previous projects (platform Ecuador), are key elements of the research framework. We specify essential datasets to apply this framework to other mountain ecosystems.

Attempted Isolation of Cryptococcus Species and Incidental Isolation of Exophiala dermatitidis from Human Oral Cavities - Caroline P. Toberna; Jessica J. F. Kram; Eric T. Beck; Sommer Ray; Tyler Gavinski; Alana K. Sterkel; Dennis J. Baumgardner (Mycopathologia, 2020)

Accuracy of fully coupled and sequential approaches for modeling hydro- and geomechanical processes - M. Beck; A. P. Rinaldi; B. Flemisch; H. Class (Computational Geosciences, 2020)
Subsurface flow and geomechanics are often modeled with sequential approaches. This can be computationally beneficial compared with fully coupled schemes, while it requires usually compromises in numerical accuracy, at least when the sequential scheme is non-iterative. We discuss the influence of the choice of scheme on the numerical accuracy and the expected computational effort based on a comparison of a fully coupled scheme, a scheme employing a one-way coupling, and an iterative scheme using a fixed-stress split for two subsurface injection scenarios. All these schemes were implemented in the numerical simulator DuMu x . This study identifies conditions of problem settings where differences due to the choice of the model approach are as important as differences in geologic features. It is shown that in particular transient and multiphase flow, effects can be causing significant deviations between non-iterative and iterative sequential schemes, which might be in the same order of magnitude as geologic uncertainty. An iterated fixed-stress split has the same numerical accuracy as a fully coupled scheme but only for a certain number of iterations which might use up the computational advantage of solving two smaller systems of equations rather than a big monolithical one.

Innovative use of animal models to advance scientific research - D. K. Meyerholz; A. P. Beck; B. Singh (Cell and Tissue Research, 2020)

Evolving challenges to model human diseases for translational research - Amanda P. Beck; David K. Meyerholz (Cell and Tissue Research, 2020)

Anti-HPV Nanoemulsified-Imiquimod: A New and Potent Formulation to Treat Cervical Cancer - Luiza Abrahão Frank; R. P. Gazzi; P. A. Mello; P. Chaves; F. Peña; R. C. R. Beck; A. Buffon; A. R. Pohlmann; Silvia S. Guterres (AAPS PharmSciTech, 2020)

Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate - Whitney R. Friedman; Benjamin S. Halpern; Elizabeth McLeod; Michael W. Beck; Carlos M. Duarte; Carrie V. Kappel; Arielle Levine; Robert D. Sluka; Steven Adler; Casey C. O’Hara; Eleanor J. Sterling; Sebastian Tapia-Lewin; et al. (Frontiers in Marine Science, 2020)

Sphingosine-coating of plastic surfaces prevents ventilator-associated pneumonia - Aaron P. Seitz; Fabian Schumacher; Jennifer Baker; Matthias Soddemann; Barbara Wilker; Charles C. Caldwell; Ryan M. Gobble; Markus Kamler; Katrin Anne Becker; Sascha Beck; Burkhard Kleuser; Michael J. Edwards; et al. (Journal of Molecular Medicine, 2019)

I just lost it! Fear and anger reduce the sense of agency: a study using intentional binding - Julia F. Christensen; S. Di Costa; B. Beck; P. Haggard (Experimental Brain Research, 2019)

Spatial and Temporal Patterns of Pore Water Chemistry in the Inter-Tidal Zone of a High Energy Beach - Hannelore Waska; J. Greskowiak; J. Ahrens; M. Beck; S. Ahmerkamp; P. Böning; H. J. Brumsack; J. Degenhardt; C. Ehlert; B. Engelen; N. Grünenbaum; M. Holtappels; et al. (Frontiers in Marine Science, 2019)

Spread, Behavior, and Ecosystem Consequences of Conventional Munitions Compounds in Coastal Marine Waters - Aaron J. Beck; Martha Gledhill; Christian Schlosser; Beate Stamer; Claus Böttcher; Jens Sternheim; Jens Greinert; Eric P. Achterberg (Frontiers in Marine Science, 2018)

Patterns or mechanisms? Bergmann’s and Rapoport’s rule in moths along an elevational gradient - J. Beck; H. C. Liedtke; S. Widler; F. Altermatt; S. P. Loader; R. Hagmann; S. Lang; K. Fiedler (Community Ecology, 2016)

Intensity-dependent EMG response for the biceps brachii during sustained maximal and submaximal isometric contractions - Joshua C. Carr; Travis W. Beck; Xin Ye; Nathan P. Wages (European Journal of Applied Physiology, 2016)

Autoantibodies to central nervous system neuronal surface antigens: psychiatric symptoms and psychopharmacological implications - T. A. Pollak; K. Beck; S. R. Irani; O. D. Howes; A. S. David; P. K. McGuire (Psychopharmacology, 2016)

Examination of a neural cross-over effect using resting mechanomyographic mean frequency from the vastus lateralis muscle in different resting positions following aerobic exercise - Nathan P. Wages; Travis W. Beck; Xin Ye; Joshua C. Carr (European Journal of Applied Physiology, 2016)

Temperate predators and seasonal water temperatures impact feeding of a range expanding tropical fish - Hayden J. Beck; David A. Feary; Ashley M. Fowler; Elizabeth M. P. Madin; David J. Booth (Marine Biology, 2016)

Effects of age on arterial stiffness and central blood pressure after an acute bout of resistance exercise - Robert S. Thiebaud; Christopher A. Fahs; Lindy M. Rossow; Jeremy P. Loenneke; Daeyeol Kim; J. Grant Mouser; Travis W. Beck; Debra A. Bemben; Rebecca D. Larson; Michael G. Bemben (European Journal of Applied Physiology, 2016)

Hidden diversity in the morphologically variable script lichen (Graphis scripta) complex (Ascomycota, Ostropales, Graphidaceae) - Ekaphan Kraichak; Robert Lücking; Andre Aptroot; Andreas Beck; Patrick Dornes; Volker John; James C. Lendemer; Matthew P. Nelsen; Gerhard Neuwirth; Aparna Nutakki; Sittiporn Parnmen; Mohammad Sohrabi; et al. (Organisms Diversity & Evolution, 2015)

Short-arm human centrifugation with 0.4g at eye and 0.75g at heart level provides similar cerebrovascular and cardiovascular responses to standing - Nandu Goswami; Michelle Bruner; Da Xu; Marie-Pierre Bareille; Arnaud Beck; Helmut Hinghofer-Szalkay; Andrew P. Blaber (European Journal of Applied Physiology, 2015)

Evidence of ancient horizontal gene transfer between fungi and the terrestrial alga Trebouxia - A. Beck; P. K. Divakar; N. Zhang; M. C. Molina; L. Struwe (Organisms Diversity & Evolution, 2015)

The effects of a remediated fly ash spill and weather conditions on reproductive success and offspring development in tree swallows - Michelle L. Beck; William A. Hopkins; Brian P. Jackson; Dana M. Hawley (Environmental Monitoring and Assessment, 2015)

The Osteology and Systematics of the Enigmatic Australian Oligo-Miocene Metatherian Yalkaparidon (Yalkaparidontidae; Yalkaparidontia; ?Australidelphia; Marsupialia) - Robin M. D. Beck; Kenny J. Travouillon; Ken P. Aplin; Henk Godthelp; Michael Archer (Journal of Mammalian Evolution, 2014)

Interactions of the human cardiopulmonary, hormonal and body fluid systems in parabolic flight - U. Limper; P. Gauger; P. Beck; F. Krainski; F. May; L. E. J. Beck (European Journal of Applied Physiology, 2014)

Vascular adaptations to low-load resistance training with and without blood flow restriction - Christopher A. Fahs; Lindy M. Rossow; Robert S. Thiebaud; Jeremy P. Loenneke; Daeyeol Kim; Takashi Abe; Travis W. Beck; Daniel L. Feeback; Debra A. Bemben; Michael G. Bemben (European Journal of Applied Physiology, 2014)

Evaluation of coagulation assays versus LC-MS/MS for determinations of dabigatran concentrations in plasma - Jovan P. Antovic; Mika Skeppholm; Jaak Eintrei; Elisabet Eriksson Boija; Lisbeth Söderblom; Eva-Marie Norberg; Liselotte Onelöv; Yuko Rönquist-Nii; Anton Pohanka; Olof Beck; Paul Hjemdahl; Rickard E. Malmström (European Journal of Clinical Pharmacology, 2013)

Spatial and Temporal Variation in the Diet of Tree Swallows: Implications for Trace-Element Exposure After Habitat Remediation - Michelle L. Beck; William A. Hopkins; Brian P. Jackson (Archives of Environmental Contamination and Toxicology, 2013)

Traditional and targeted exome sequencing reveals common, rare and novel functional deleterious variants in RET-signaling complex in a cohort of living US patients with urinary tract malformations - Rajshekhar Chatterjee; Enrique Ramos; Mary Hoffman; Jessica VanWinkle; Daniel R. Martin; Thomas K. Davis; Masato Hoshi; Stanley P. Hmiel; Anne Beck; Keith Hruska; Doug Coplen; Helen Liapis; et al. (Human Genetics, 2012)

Outcomes of a systems-level intervention offering breast cancer risk assessments to low-income underserved women - Darren Mays; McKane E. Sharff; Tiffani A. DeMarco; Bernice Williams; Beth Beck; Vanessa B. Sheppard; Beth N. Peshkin; Jennifer Eng-Wong; Kenneth P. Tercyak (Familial Cancer, 2012)

The functional genomics of an eco‐evolutionary feedback loop: linking gene expression, trait evolution, and community dynamics - Lutz Becks; Stephen P. Ellner; Laura E. Jones; Nelson G. Hairston (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 492–501 Abstract Feedbacks between ecological and evolutionary change may play important roles in community and ecosystem functioning, but a complete eco‐evolutionary feedback loop has not been demonstrated at the community level, and we know little about molecular mechanisms underlying this kind of eco‐evolutionary dynamics. In predator–prey (rotifer‐alga) microcosms, cyclical changes in predator abundance generated fluctuating selection for a heritable prey defence trait, cell clumping. Predator population growth was affected more by prey evolution than by changes in prey abundance, and changes in predator abundance drove further prey evolution, completing the feedback loop. Within a predator–prey cycle, genes up‐regulated as clumping declined were down‐regulated as clumping increased, and vice‐versa. Genes changing most in expression tended to be associated with defence or its cost. Expression patterns of individual genes differed greatly between consecutive cycles (often reversing direction), suggesting that a particular phenotype may be produced by several (perhaps many) different gene transcription pathways.

Variability in pulmonary function following rapid altitude ascent to the Amundsen–Scott South Pole station - S. Lalande; P. J. Anderson; A. D. Miller; M. L. Ceridon; K. C. Beck; K. A. O’Malley; J. B. Johnson; B. D. Johnson (European Journal of Applied Physiology, 2011)

Rapid prey evolution and the dynamics of two-predator food webs - Stephen P. Ellner; Lutz Becks (Theoretical Ecology, 2011)

Characterization of Bacterial Isolates Collected from a Sheep Model of Osseointegration - Dustin L. Williams; Roy D. Bloebaum; James P. Beck; Cathy A. Petti (Current Microbiology, 2010)

Cultivation‐independent characterization of ‘ Candidatus Magnetobacterium bavaricum’ via ultrastructural, geochemical, ecological and metagenomic methods - C. Jogler; M. Niebler; W. Lin; M. Kube; G. Wanner; S. Kolinko; P. Stief; A. J. Beck; D. de Beer; N. Petersen; Y. Pan; R. Amann; et al. (Environmental Microbiology, 2010)
Summary ‘ Candidatus Magnetobacterium bavaricum’ is unusual among magnetotactic bacteria (MTB) in terms of cell size (8–10 µm long, 1.5–2 µm in diameter), cell architecture, magnetotactic behaviour and its distinct phylogenetic position in the deep‐branching Nitrospira phylum. In the present study, improved magnetic enrichment techniques permitted high‐resolution scanning electron microscopy and energy dispersive X‐ray analysis, which revealed the intracellular organization of the magnetosome chains. Sulfur globule accumulation in the cytoplasm point towards a sulfur‐oxidizing metabolism of ‘ Candidatus M. bavaricum’. Detailed analysis of ‘ Candidatus M. bavaricum’ microhabitats revealed more complex distribution patterns than previously reported, with cells predominantly found in low oxygen concentration. No correlation to other geochemical parameters could be observed. In addition, the analysis of a metagenomic fosmid library revealed a 34 kb genomic fragment, which contains 33 genes, among them the complete rRNA gene operon of ‘ Candidatus M. bavaricum’ as well as a gene encoding a putative type IV RubisCO large subunit.

Reduction of adaptive genetic diversity radically alters eco‐evolutionary community dynamics - Lutz Becks; Stephen P. Ellner; Laura E. Jones; Nelson G. Hairston Jr (Ecology Letters, 2010)
Ecology Letters (2010) 13: 989–997 Abstract Adaptive variation in the traits determining ecological interactions can lead to evolution so rapid that ecological dynamics change course while in progress (i.e., ‘eco‐evolutionary dynamics’). However, little is known about how the qualitative properties of eco‐evolutionary dynamics (e.g., cycling, equilibrium, etc.) are affected by the amount of heritable variation present. Here, we show that a change in the range of variation in a heritable prey defense trait determines what dynamics are observed in an experimental predator–prey system. We combine modelling and laboratory experiments to show that initial defense trait variation determines whether populations exhibit eco‐evolutionary cycles in which heritable variation is maintained, or converge to an equilibrium at which the prey population becomes monomorphic. Our results show how small changes in the amount of adaptive genetic variance initially present can radically alter eco‐evolutionary dynamics, and can ultimately determine whether heritable variation is maintained or lost.

Measurements and products from the Solar Backscatter Ultraviolet (SBUV/2) and Ozone Mapping and Profiler Suite (OMPS) instruments - L. E. Flynn; D. McNamara; C. T. Beck; I. Petropavlovskikh; E. Beach; Y. Pachepsky; Y. P. Li; M. Deland; L. -K. Huang; C. S. Long; R. Tiruchirapalli; S. Taylor (International Journal of Remote Sensing, 2009)

A comparison of critical force and electromyographic fatigue threshold for isometric muscle actions of the forearm flexors - C. Russell Hendrix; Terry J. Housh; Glen O. Johnson; Joseph P. Weir; Travis W. Beck; Moh H. Malek; Michelle Mielke; Richard J. Schmidt (European Journal of Applied Physiology, 2009)

Displaying remotely sensed vegetation dynamics along natural gradients for ecological studies - P. S. A. Beck; T. J. Wang; A. K. Skidmore; X. H. Liu (International Journal of Remote Sensing, 2008)

Trace eyeblink conditioning in patients with cerebellar degeneration: comparison of short and long trace intervals - M. Gerwig; A. C. Eßer; H. Guberina; M. Frings; F. P. Kolb; M. Forsting; V. Aurich; A. Beck; D. Timmann (Experimental Brain Research, 2008)

A ground‐validated NDVI dataset for monitoring vegetation dynamics and mapping phenology in Fennoscandia and the Kola peninsula - P. S. A. Beck; P. Jönsson; K.‐A. Høgda; S. R. Karlsen; L. Eklundh; A. K. Skidmore (International Journal of Remote Sensing, 2007)

Frequency and within‐type variations of large‐scale circulation types and their effects on low‐frequency climate variability in central europe since 1780 - C. Beck; J. Jacobeit; P. D. Jones (International Journal of Climatology, 2007)
This study investigates the importance of large‐scale atmospheric circulation changes for Central European climate variations during the last two centuries. On the basis of an objective classification of monthly mean sea level pressure (SLP) grids reconstructed back to 1780 and monthly historical station data for the same period, temperature and precipitation changes in Central Europe since 1780 are decomposed into two parts; one part due to frequency changes of large‐scale circulation types, and the other part caused by (dynamic and climatic) changes within these circulation types. This is achieved by applying a particular decomposition scheme for moving 31‐year time windows during the 1780–1995 period. Results indicate that large parts of the long‐term variations in Central European climate cannot be explained sufficiently by frequency changes of circulation types. Roughly one half of these variations—even up to 80% during July—can be ascribed to varying internal properties of some major circulation types. Percentages of frequency‐related and within‐type‐related climate changes are seen to vary on decadal to multidecadal time scales, thus implying that relationships between large‐scale circulation patterns and regional climates are characterised by distinct instationarities. Furthermore, regional climate variations, being attributable to within‐type changes of major circulation types, can only partly be explained by corresponding variations in dynamic properties (vorticity, intensity) of these circulation types. This points to the importance of further sources for within‐type variability, including subgrid‐scale processes, synoptic‐scale variations, and modifications of the climatic boundary conditions. Copyright © 2006 Royal Meteorological Society.

Possible effects of the 2004 and 2005 hurricanes on manatee survival rates and movement - C. A. Langtimm; M. D. Krohn; J. P. Reid; B. M. Stith; C. A. Beck (Estuaries and Coasts, 2006)

Seasonality of weather and tree phenology in a tropical evergreen mountain rain forest - J. Bendix; J. Homeier; E. Cueva Ortiz; P. Emck; S. -W. Breckle; M. Richter; E. Beck (International Journal of Biometeorology, 2006)

The April 9, 2001 Juan Fernández Ridge (M w 6.7) Tensional Outer-Rise Earthquake and its Aftershock Sequence - R. Fromm; P. Alvarado; S. L. Beck; G. Zandt (Journal of Seismology, 2006)

Spatial Prediction of Invasion Success Across Heterogeneous Landscapes using an Individual-Based Model - Sarah C. Goslee; Debra P. C. Peters; K. George Beck (Biological Invasions, 2006)

An improved polyclonal antiserum for detecting Ryegrass mosaic rymovirus - D. E. Webster; D. L. Beck; F. Rabenstein; R. L. S. Forster; P. L. Guy (Archives of Virology, 2005)

The acute effects of static stretching on peak torque, mean power output, electromyography, and mechanomyography - J. T. Cramer; T. J. Housh; J. P. Weir; G. O. Johnson; J. W. Coburn; T. W. Beck (European Journal of Applied Physiology, 2005)

Aquaporin expression is downregulated in a murine model of colitis and in patients with ulcerative colitis, Crohn’s disease and infectious colitis - J. A. Hardin; L. E. Wallace; J. F. K. Wong; E. V. O’Loughlin; S. J. Urbanski; D. G. Gall; W. K. MacNaughton; P. L. Beck (Cell and Tissue Research, 2004)

Nosocomial nontyphoidal salmonellosis after antineoplastic chemotherapy: reactivation of asymptomatic colonization? - J. Delaloye; G. Merlani; C. Petignat; A. Wenger; K. Zaman; C. Monnerat; O. Matzinger; M. Beck Popovic; P. Vuichard; N. Ketterer; P. E. Tarr (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Cellular Uptake But Low Permeation of Human Calcitonin-Derived Cell Penetrating Peptides and Tat(47-57) Through Well-Differentiated Epithelial Models - Rachel Tréhin; Ulrike Krauss; Annette G. Beck-Sickinger; Hans P. Merkle; Hanne M. Nielsen (Pharmaceutical Research, 2004)

The influence of formulation and spacer device on the in vitro performance of solution chlorofluorocarbon-free propellant-driven metered dose inhalers - Hugh D. C. Smyth; Vance P. Beck; Dennis Williams; Anthony J. Hickey (AAPS PharmSciTech, 2004)

The influence of formulation and spacer device on the in vitro performance of solution chlorofluorocarbon-free propellant-driven metered dose inhalers - Hugh D. C. Smyth; Vance P. Beck; Dennis Williams; Anthony J. Hickey (AAPS PharmSciTech, 2004)

Cellular Internalization of Human Calcitonin Derived Peptides in MDCK Monolayers: A Comparative Study with Tat(47-57) and Penetratin(43-58) - Rachel Tréhin; Ulrike Krauss; Roman Muff; Martina Meinecke; Annette G. Beck-Sickinger; Hans P. Merkle (Pharmaceutical Research, 2004)

Broad distribution of crystal-field environments for Nd 3+ in calcite - S. H. Withers; R. E. Peale; A. F. Schulte; G. Braunstein; K. M. Beck; W. P. Hess; R. J. Reeder (Physics and Chemistry of Minerals, 2003)

Evolution of clay mineral assemblages and organic matter in the late glacial-Holocene sedimentary infill of Lake Annecy, (northwestern Alps): paleoenvironmental implications - F. Manalt; C. Beck; J.-R. Disnar; J.-F. Deconinck; P. Recourt (Journal of Paleolimnology, 2001)

Modeling and estimation of C 1- P 1 bias in GPS receivers - Y. Gao; F. Lahaye; P. Hroux; X. Liao; N. Beck; M. Olynik (Journal of Geodesy, 2001)

Monthly mean pressure reconstruction for the Late Maunder Minimum Period (AD 1675-1715) - J. Luterbacher; R. Rickli; C. Tinguely; E. Xoplaki; E. Schpbach; D. Dietrich; J. Hsler; M. Ambhl; C. Pfister; P. Beeli; U. Dietrich; A. Dannecker; et al. (International Journal of Climatology, 2000)

Monthly mean pressure reconstruction for the Late Maunder Minimum Period (AD 1675–1715) - J. Luterbacher; R. Rickli; C. Tinguely; E. Xoplaki; E. Schüpbach; D. Dietrich; J. Hüsler; M. Ambühl; C. Pfister; P. Beeli; U. Dietrich; A. Dannecker; et al. (International Journal of Climatology, 2000)

Workplace drug testing (WDT) likely to increase in Europe - P. Dalén; O. Beck; U. Bergman; P. Björklöv; D. Finer; M. Garle; F. Sjöqvist (European Journal of Clinical Pharmacology, 2000)

The major and a minor class II β-chain (B-LB ) gene flank the Tapasin gene in the B-F /B-L region of the chicken major histocompatibility complex - J. P. Jacob; S. Milne; S. Beck; J. Kaufman (Immunogenetics, 2000)

Distribution and diversity of New Zealand isolates of ryegrass mosaic virus - D. E. Webster; P. L. Guy; D. L. Beck; R. L. S. Forster (Archives of Virology, 1999)

Fractal geometry of root systems: Field observations of contrasting genotypes of common bean (Phaseolus vulgaris L.) grown under different phosphorus regimes - Kai L. Nielsen; Carter R. Miller; Douglas Beck; Jonathan P. Lynch (Plant and Soil, 1999)

Human parvovirus B19 infection in acute fulminant liver failure - Y. V. Karetnyi; P. R. Beck; R. S. Markin; A. N. Langnas; S. J. Naides (Archives of Virology, 1999)

Rated well-being in relation to plasma concentrations of l - and d -methadone in satisfied and dissatisfied patients on methadone maintenance treatment - A. J. Hiltunen; O. Beck; P. Hjemdahl; P. Liljeberg; U. Almstrm; K. Brodin; J. von Wachenfeldt; S. Borg (Psychopharmacology, 1999)

Monthly mean pressure reconstructions for Europe for the 1780–1995 period - P.D. Jones; T.D. Davies; D.H. Lister; V. Slonosky; T. Jónsson; L. Bärring; P. Jönsson; P. Maheras; F. Kolyva‐Machera; M. Barriendos; J. Martin‐Vide; R. Rodriguez; et al. (International Journal of Climatology, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

Short tandem repeat polymorphic markers for the rat genome from marker-selected libraries - Roxanne Y. Walder; Michael R. Garrett; Ann M. McClain; Gretel E. Beck; Theresa M.H. Brennan; Nancy A. Kramer; Adam B. Kanis; Allyn L. Mark; John P. Rapp (Mammalian Genome, 1998)

Characterization of rat lung ICAM-1 - B. Beck-Schimmer; R. C. Schimmer; H. Schmal; C. M. Flory; H. P. Friedl; T. Pasch; P. A. Ward (Inflammation Research, 1998)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Correlation between plasma clozapine concentration and heart rate variability in schizophrenic patients - Thomas Rechlin; Georg Beck; Maria Weis; Wolfgang P. Kaschka (Psychopharmacology, 1998)

Tropospheric Ozone Research (TOR) A Sub-Project of EUROTRAC - D. Kley; J. Beck; P. I. Grennfelt; ø. Hov; S. A. Penkett (Journal of Atmospheric Chemistry, 1997)

Molecular analysis of Gaucher disease: distribution of eight mutations and the complete gene deletion in 27 patients from Germany - P. le Coutre; A. Demina; Ernest Beutler; Michael Beck; P. E. Petrides (Human Genetics, 1997)

Influence of inoculation with arbuscular mycorrhizal fungi on stable isotopes of nitrogen in Phaseolus vulgaris - D. Redecker; P. von Berswordt-Wallrabe; D. P. Beck; D. Werner (Biology and Fertility of Soils, 1997)

Differential ?- and ?-adrenergic activation during psychological stress - P. Montoya; Stuart Brody; Katja Beck; Ralf Veit; Harald Rau (European Journal of Applied Physiology, 1997)

Use of SSCP analysis to identify germline mutations in HNPCC families fulfilling the Amsterdam criteria - N. E. Beck; I. P. M. Tomlinson; Tessa Homfray; I. Frayling; Shirley V. Hodgson; Chris Harocopos; Walter F. Bodmer (Human Genetics, 1997)

Expression ofnef, vpu, CA and CD4 during the infection of lymphoid and monocytic cell lines with HIV-1 - T. Schneider; P. Hildebrandt; K. Rokos; U. Schubert; W. Rnspeck; C. Grund; A. Beck; R. Blesken; G. Kulins; H. Oldenburg; G. Pauli (Archives of Virology, 1992)

Variations of heavy metals and arsenic in fish and other organisms from the Calcasieu River and Lake, Louisiana - G. J. Ramelow; C. L. Webre; C. S. Mueller; J. N. Beck; J. C. Young; M. P. Langley (Archives of Environmental Contamination and Toxicology, 1989)